Au/CdS Nanocomposite through Digestive Ripening of Au and CdS Nanoparticles and Its Photocatalytic Activity. Issue 23 (20th June 2018) - Bhaskar, Srilakshmi P.; Karthika, Minikumari S.; Jagirdar, Balaji R.
Abstract: Co‐digestive ripening is a versatile strategy for the preparation of binary metal nanoparticles such as core‐shell, composites, and alloys. The mechanism of co‐digestive ripening is hypothesized to involve inter‐atom transfer facilitated by capping agents. In this work, co‐digestive ripening of a metal (Au) and a semiconductor (CdS) system has been presented. This process involves co‐refluxing of a physical mixture of Au and CdS colloids in presence of hexadecyl amine (HDA) in mesitylene solvent. Individual colloids of Au and CdS were prepared by solvated metal atom dispersion (SMAD) method. The growth control of nanoparticles using HDA resulted in the formation of monodisperse particles via a room temperature digestive ripening process. Au/CdS nanocomposite obtained via co‐digestive ripening strategy was characterized by a matrix‐like structure made up of CdS nanoparticles in which Au nanoparticles were embedded. CdS nanoparticles were found to establish an intimate surface contact with Au nanoparticles and the matrix of CdS surrounding Au was developed via aggregation during co‐refluxing. Formation of the Au/CdS nanocomposite is proposed to involve a ligand replacement process wherein HDA molecules capping the Au surface are displaced by CdS owing to strong Au‐CdS interaction. The Au/CdS composite thus obtained showed superior photocatalytic activity compared to pure CdS nanoparticles for dye degradation reaction. Abstract : CdS encapsulated Au for photocatalysis: The Au/CdS nanocomposite, prepared through digestive ripening strategy showed Au in a matrix‐like structure made of aggregated CdS nanoparticles. The intimate surface contact between Au and CdS was verified by PL spectroscopy, XPS and TEM techniques. The hetero structure demonstrated enhanced activity in photocatalysis compared to its individual components.